Assessment and validation of a novel fast fully automated artificial intelligence left ventricular ejection fraction quantification software. Issue 3 (17th February 2022) - Samtani, Rajeev; Bienstock, Solomon; Lai, Ashton C.; Liao, Steve; Baber, Usman; Croft, Lori; Stern, Eric; Beerkens, Frans; Ting, Peter; Goldman, Martin E.
Abstract: Background: Quantification of left ventricular ejection fraction (LVEF) by transthoracic echocardiography (TTE) is operator‐dependent, time‐consuming, and error‐prone. LVivoEF by DIA is a new artificial intelligence (AI) software, which displays the tracking of endocardial borders and rapidly quantifies LVEF. We sought to assess the accuracy of LVivoEF compared to cardiac magnetic resonance imaging (cMRI) as the reference standard and to compare LVivoEF to the standard‐of‐care physician‐measured LVEF (MD‐EF) including studies with ultrasound enhancing agents (UEAs). Methods: In 273 consecutive patients, we compared MD‐EF and AI‐derived LVEF to cMRI. AI‐derived LVEF was obtained from a non‐UEA four‐chamber view without manual correction. Thirty‐one patients were excluded: 25 had interval interventions or incomplete TTE or cMRI studies and six had uninterpretable non‐UEA apical views. Results: In the 242 subjects, the correlation between AI and cMRI was r = .890, similar to MD‐EF and cMRI with r = .891 ( p  = 0.48). Of the 126 studies performed with UEAs, the correlation of AI using the unenhanced four‐chamber view was r = .89, similar to MD‐EF with r = .90. In the 116 unenhanced studies, AI correlation was r = .87, similar to MD‐EF with r = .84. From Bland‐Altman analysis, LVivoEF underreported the LVEF with a bias of 3.63 ± 7.40% EF points compared to cMRI while MD‐EF to cMRI had a bias of .33 ± 7.52% ( p  = 0.80). Conclusions: Compared to cMRI, LVivoEF can accurately quantify LVEF from a standard apical four‐chamber view without manual correction. Thus, LVivoEF has the ability to improve and expedite LVEF quantification.